Macronyssus flavus - Orlova, Maria V.; Anisimov, Nikolay V. (Zenodo, 2023)
Macronyssus flavus (Kolenati, 1856) Distribution – Russia (Bregetova 1956; Stanyukovich 1990), Europe (Dusbábek 1964; Radovsky 1967), Caucasus (Dagestan republic) (Orlova et al. 2020b), Asia (Kazakhstan, Kyrgyzstan, China) (Senotrusova 1968, Rybin 1983, Gu and Wang 1985). Hosts – Nyctalus noctule (Dusbábek 1964; Radovsky 1967; Haitlinger and Ruprecht, 1992), N. leisleri and N. lasiopterus (Stanyukovich 1997), Myotis myotis (Dusbábek 1964; Radovsky 1967), My. mystacinus (Bregetova 1956), My. daubentonii (Bregetova 1956; Dusbábek 1964), My. blythi (Stanyukovich 1997), My. nattereri (Stanyukovich 1997), Barbastella barbastellus (Dusbábek 1964), Pipistrellus pipistellus (Dusbábek 1964; Radovsky 1967), Pi. nathusii (Bregetova 1956), Verspertilio murinus (Bregetova 1956), Eptesicus nillsoni (Bregetova 1956). Published as part of Orlova, Maria V. & Anisimov, Nikolay V., 2023, Three new species of bat-parasitic gamasid mites of the genera Spinturnix, Macronyssus and Steatonyssus (Acari: Mesostigmata: Spinturnicidae, Macronyssidae) from Siberia and Mongolia, with keys to species of Russia and adjacent countries, pp. 211-239 in Persian Journal of Acarology 12 (2) on page 224, DOI:10.22073/pja.v12i2.76740, http://zenodo.org/record/8113590